2009
DOI: 10.1542/peds.2008-2498
|View full text |Cite
|
Sign up to set email alerts
|

Policies and Characteristics of the Preschool Environment and Physical Activity of Young Children

Abstract: Objectives-The preschools that children attend influence their physical activity level. But, little is known about which characteristics of a preschool may influence the physical activity of children. The purpose of this study was to examine policies and characteristics of preschools and the extent to which they influence the physical activity of 3-to 5-year-old children during the preschool day.Methods-A total of 299 children from 20 preschools wore ActiGraph (Pensacola, FL) accelerometers an average of 8.1 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
203
7
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(231 citation statements)
references
References 14 publications
13
203
7
8
Order By: Relevance
“…Periods of non-wear time of 60 consecutive minutes during which a "0" was recorded were interpreted as "activity monitor not worn," and removed from the summation of activity. 7,20,21 Weekdays on which the child did not attend preschool and weekend days were excluded. PA data from a European study indicated that during preschool attendance the children were more physically active during the afternoon hours.…”
Section: Data Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Periods of non-wear time of 60 consecutive minutes during which a "0" was recorded were interpreted as "activity monitor not worn," and removed from the summation of activity. 7,20,21 Weekdays on which the child did not attend preschool and weekend days were excluded. PA data from a European study indicated that during preschool attendance the children were more physically active during the afternoon hours.…”
Section: Data Reductionmentioning
confidence: 99%
“…Whereas the overall quality of the preschool seems to be a consistent potential correlate of preschool children' s MVPA level during preschool time, 7,8,16 inconsistent results are reported for other preschool correlates, such as the size of the playground, regardless of testing the association in relation to the children' s total 7,9,10 or playground-specific MVPA level. 5,15,17 Few large-cluster, randomized, controlled intervention studies have targeted potential correlates of physical activity (PA) at the preschool level, and so far for those that have, there has not yet been any effect.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…It is possible to produce positive impacts within the school, building self-esteem, and healthy habits and behavior in all members of the school community. 1,2,11 This study identifi ed both underweight and overweight, including obese, students in the intervention and the control group. Interventions are recommended to prevent these nutritional problems progressing, and the school is an appropriate place for these actions.…”
Section: Discussionmentioning
confidence: 99%
“…In Ireland, the National Association for Sport and Physical Education guidelines have been adopted for use in the child-care setting (80) . It has been reported that the pre-school attended, its quality level and the presence of policy are all determinants of physical activity (81)(82)(83)(84) .…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%